Fine-tuning of Terahertz resonances in hydrogen-bonded organic molecular complexes - Dash, Jyotirmayee; Ray, Shaumik; Devi, Nirmala; Basutkar, Nitin; Ambade, Ashootosh V.; Pesala, Bala (Journal of Molecular Structure, 2019)
Novel organic molecular complexes have been designed and synthesized to obtain prominent Terahertz (THz) resonances in the low-frequency region. Intermolecular hydrogen bonds give rise to low-frequency THz resonances and hence binary organic molecular complexes of pyridyl alkylamide/benzamide (DAP) and hexyl thymine (C6THY) with multiple strong intermolecular hydrogen bonds (N-H–-O and N-H–-N) are designed and synthesized. THz resonances of the complexes are fine-tuned by varying the number of benzene rings in the DAP moiety (PrDAP + C6THY, PrPhDAP + C6THY and PhDAP + C6THY). DFT simulation studies of two molecule clusters have been carried out to understand the origin of low-frequency THz resonances. It has been observed that the lowest THz resonances (< 2 THz) originate due to translation/rotation of the whole crystal structure and the resonances from 2 to 4 THz are mainly due to intermolecular hydrogen bond bending/stretching vibrations. In order to understand the individual hydrogen bond strengths, compliance constants, which are inverse of the force constants are calculated and Natural Bond Orbital (NBO) analysis has been carried out. Comparison of the experimental THz spectra of different complexes shows that there is a small but tunable variation in THz resonances from one complex to another. Tuning of THz resonances has potential applications in designing THz tags, which can be used in various anti-counterfeiting applications such as currency notes, pharmaceutical tablets. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Compliance constant; Natural bond orbital analysis; Organic molecular complex; Terahertz spectroscopy